1980
DOI: 10.1246/bcsj.53.703
|View full text |Cite
|
Sign up to set email alerts
|

The Coextraction of Water into Nitrobenzene with Alkali and Alkaline Earth Metal Salts of 2,2′,4,4′,6,6′-Hexanitrodiphenylamine in the Presence of Several Crown Ethers and Cryptands

Abstract: Alkali and alkaline earth metal salts of 2,2′,4,4′,6,6′-hexanitrodiphenylamine (HND) were extracted into nitrobenzene in the absence or presence of several crown ethers or cryptands which differ from one another in hole size. The quantity of water transferred to the nitrobenzene phase was determined by means of the Karl-Fischer method. The NMR and near-infrared spectra show that the coextraction of water is caused by the hydration of the cations. The number of water molecules attached to the cations increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 14 publications
3
27
0
1
Order By: Relevance
“…This is supported by the fact that the number (0.8) of water molecules co-extracted with Na(B15C5) + into nitrobenzene is somewhat smaller than that (1.1) with Na(B18C6) + . 13 Table 1, together with the component equilibrium constants, 1,2,14,15 which correspond to each system. It is clear that a difference in log Kex between the MnO4 -and tfa -extraction systems is mainly due to that in log KD,Na(15C5)A between them.…”
Section: Ion-pair Formation Of Natfa and Naltfa Complexes In Watermentioning
confidence: 99%
“…This is supported by the fact that the number (0.8) of water molecules co-extracted with Na(B15C5) + into nitrobenzene is somewhat smaller than that (1.1) with Na(B18C6) + . 13 Table 1, together with the component equilibrium constants, 1,2,14,15 which correspond to each system. It is clear that a difference in log Kex between the MnO4 -and tfa -extraction systems is mainly due to that in log KD,Na(15C5)A between them.…”
Section: Ion-pair Formation Of Natfa and Naltfa Complexes In Watermentioning
confidence: 99%
“…The water molecule bound to the crown ether complex is that hydrated to the central metal ion. 14,17 It is well known that K + has the optimal size to fit into the cavity of the 18-membered ring crown ethers. Therefore, the small value of nH2O,KL for the KL + complex can be interpreted by the model that the B18C6 molecule conceals K + and thus the water molecule can not satisfactorily interact with K + in the complex.…”
Section: Hydration Number Of the B18c6-k + Complexmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Particularly, in the solvent extraction study, since the solutes in the water-saturated organic solution are discussed, hydration of the solutes in the organic phase is a very important subject. It has been demonstrated that the water molecules are coextracted with the metal ions, [11][12][13][14] the metal complexes, [14][15][16][17] and the inorganic anions 2,3,[18][19][20] into the organic solvents, and the mean hydration numbers of these solutes in the organic phase were determined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations